2021
DOI: 10.1007/s00146-021-01325-7
|View full text |Cite
|
Sign up to set email alerts
|

Artificial virtuous agents: from theory to machine implementation

Abstract: Virtue ethics has many times been suggested as a promising recipe for the construction of artificial moral agents due to its emphasis on moral character and learning. However, given the complex nature of the theory, hardly any work has de facto attempted to implement the core tenets of virtue ethics in moral machines. The main goal of this paper is to demonstrate how virtue ethics can be taken all the way from theory to machine implementation. To achieve this goal, we critically explore the possibilities and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 95 publications
(88 reference statements)
0
15
0
Order By: Relevance
“…It draws on a combination of insights from previous work, in particular the weight analogy of Thornton et al. (2016), the classification method of Guarini (2006), the "dispositional functionalism" explored by Howard and Muntean (2017), and the eudaimonic approach to "android arete" proposed by Coleman (2001) and Stenseke (2021). Essentially, the model is based on the idea that dispositional virtues can be functionally carried out by artificial neural networks that, in the absence of a moral exemplar, learn from experience in light of an eudaimonic reward by means of a phronetic learning system.…”
Section: Artificial Virtuous Agentsmentioning
confidence: 99%
See 4 more Smart Citations
“…It draws on a combination of insights from previous work, in particular the weight analogy of Thornton et al. (2016), the classification method of Guarini (2006), the "dispositional functionalism" explored by Howard and Muntean (2017), and the eudaimonic approach to "android arete" proposed by Coleman (2001) and Stenseke (2021). Essentially, the model is based on the idea that dispositional virtues can be functionally carried out by artificial neural networks that, in the absence of a moral exemplar, learn from experience in light of an eudaimonic reward by means of a phronetic learning system.…”
Section: Artificial Virtuous Agentsmentioning
confidence: 99%
“…Learning from moral exemplars could also be achieved given that the agent has (i) some way of identifying and adopting suitable exemplars and (ii) some way of learning from them. Besides the solutions offered by Govindarajulu et al (2019) and Berberich and Diepold (2018), Stenseke (2021) has suggested that exemplars can be identified through e-type and e value. Specifically, an agent a takes another agent b as a moral exemplar iff (1) a and b share the same e-type and (2) b has a higher e-value than a.…”
Section: Artificial Virtuous Agentsmentioning
confidence: 99%
See 3 more Smart Citations